2022
DOI: 10.3390/catal12030306
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electrochemical Sensing Platform for the Sensitive Detection and Degradation Monitoring of Methylene Blue

Abstract: Methylene blue is a toxic dye that is extensively used as a colorant in textile industries. Industrial effluent containing methylene blue, when drained into water bodies without proper treatment, poses a serious threat to aquatic and human lives. In order to protect the biocycle, various methods have been established to detect and remove hazardous dyes from aqueous systems. Electrochemical methods are preferred, owing to their characteristic features of simplicity, portability, potential selectivity, cost effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…This result is in reasonable agreement with previously reported literature for this ATP E-AB sensor on a 2 mm Au disk electrode . It was also observed that the peak shifted to a more positive potential with increasing ATP concentration (Figure a), which was attributed to a decrease in the solution pH. , …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in reasonable agreement with previously reported literature for this ATP E-AB sensor on a 2 mm Au disk electrode . It was also observed that the peak shifted to a more positive potential with increasing ATP concentration (Figure a), which was attributed to a decrease in the solution pH. , …”
Section: Resultssupporting
confidence: 93%
“…24 It was also observed that the peak shifted to a more positive potential with increasing ATP concentration (Figure 1a), which was attributed to a decrease in the solution pH. 33,34 The DA aptasensor had a K d value of 8 μM, an LOD of 0.1 μM, and a linear range of 0.1−10 μM, which is within the physiologically relevant concentrations of DA, i.e., the normal range is 0.1−1 μM, 35 while for patients treated with L-DOPA, the range is elevated to 0.9−6 μM. 36 The ST sensor had an LOD of 0.5 μM, a linear range of 0.5−10 μM, and a K d value of 14 μM.…”
Section: ■ Experimental Sectionmentioning
confidence: 88%
“…Among the approaches mentioned above, the electrochemical degradation route is more expensive than other approaches for dye degradation [ 199 ]. The main reason for reduced implementation of the electrochemical approach is high energy consumption, the requirement for more chemicals, and costly equipment [ 200 , 201 ]. Other challenges in implementing the electrochemical approach are the production of metabolites and other by-products during these processes.…”
Section: Chemical Degradation Approaches For Water-soluble Dyes and N...mentioning
confidence: 99%
“…Industrial wastewater contains harmful compounds that have an inimical impact on humans, animals, plants, and aquatic life. [38,39] It is crucial to remove the pollutants from wastewater or convert it into less harmful chemicals because it lowers the biological oxygen demand of water when directly discharged into water bodies, particularly those that contain methylene blue (MB). [40] Another dye that causes infections of the gastrointestinal tract, skin, respiratory tract, and eyes is rhodamine B (RhB), which is categorized as a neurotoxin and carcinogenic dye for humans.…”
Section: Introductionmentioning
confidence: 99%